EFFECTS OF POLYSACCHARIDES FROM GYNOSTEMMA PENTAPHYLLUM (THUNB.), MAKINO ON PHYSICAL FATIGUE - Shan, Linna; Yong-Xiu, Shi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Gynostemma pentaphyllum (Thunb.) Makino has been reported to have a wide range of health benefits in Chinese herbal medicines. Polysaccharides from Gynostemma pentaphyllum (PGP), has been identified as one of the active ingredients responsible for its biological activities. Although many pharmacological activities of PGP have received a great deal of attention, there is limited evidence for the anti-fatigue effects of PGP. The purpose of this study was to investigate the effects of polysaccharides from PGP on physical fatigue. Materials and method: The rats were divided into four groups, with 10 animals per group: control (C), group, low-treated (LT), group, medium-treated (MT), group, and high-treated (HT), group. The C group received distilled water, while LT, MT and HT groups were given various doses of PGP (100, 200, 400 mg/kg• d). After 30 days, forced swimming test was carried out in an acrylic plastic pool, then the exhaustive swimming time of rats and some biochemical parameters related to fatigue were measured. The data obtained showed that PGP could extend the exhaustive swimming time of the rats, as well as decrease the blood lactic acid (BLA), and blood urea nitrogen (BUN), concentrations, and increase the hemoglobin, liver glycogen and muscle glycogen concentrations. Result: The data obtained showed that different doses of PGP could extend the exhaustive swimming time of the rats, as well as decrease the BLA and BUN concentrations, and increase the hemoglobin, liver glycogen and muscle glycogen concentrations, which suggests that PGP had significant anti-fatigue effects on rats. Conclusion: PGP may be of use as a potential anti-fatigue agent, but there is a need for further research on long-term use in order to show its positive effects on physical fatigue.